Assembly of phase transferred nickel nanoparticles at air-water interface using Langmuir-Blodgett technique - Bala, Tanushree; Joshi, Bhagyashree; Iyer, Neelima; Sastry, Murali; Bhagavatula L. V. Prasad (Journal of Nanoscience and Nanotechnology, 2006)
Development of simple and efficient protocol for the synthesis of Ni nanoparticles in aqueous media and their subsequent phase transfer to organic media is reported. The synthesis of nickel nanoparticles in aqueous medium is accomplished by reducing the nickel nitrate with sodium borohydricle in presence of oleic acid. It results in the formation of nickel nanoparticles capped with oleic acid. The pristine oleic acid capped nickel nanoparticles were then phase transferred to nonpolar solvents such as toluene using stearic acid. The phase transfer was effective probably due to the space exchange between the oleic acid moiety and stearic acid molecules. The hydrophobized Ni thus obtained was organized at the air-water interface and it was observed that by controlling the pressure and concentration of hydrophobized Ni nanoparticles at air-water interface, linear ribbon like assemblies could be obtained. The organization process was followed by surface pressure-area isotherm measurement and Brewster Angle Microscopy.
Keywords: assembly; Langmuir-Blodgett technique; Ni nanoparticles; Phase transfer